TERRITORIAL ORGANIZATION OF KINGDOM OF SERBS, CROATS AND SLOVENES (KINGDOM OF YUGOSLAVIA) - Stankovic, Marko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The paper analyzes territorial organization of the Kingdom of Serbs, Croats and Slovenes, i.e. the Kingdom of Yugoslavia. After a brief review of the emergence of that country, which largely influenced its territorial organization, the systems of territorial organization in both of its constitutions– the “Vidovdan” Constitution and the “September” Constitution – were analyzed. Finally, there is a short evaluation of the degree of self-government that these systems envisioned. Key words: – Kingdom of Serbs, Croats and Slovenes. – Territorial organization. – The Vidovdan Constitution. – The September Constitution. – Local self-government.